Comparison of Side Effects between Different Brands of COVID-19 Vaccines among Malaysia Adult Population - Faculty of Pharmacy & Health Sciences; Aina Amanina Abdul Jalil; Ahmad Yasser Hamdi Nor Azlan (Asian Journal of Medicine & Health Sciences, 2023)
In January 2020, COVID-19 was declared a public health emergency of international concern that targets the human respiratory system and engulfs the entire world into a pandemic lifestyle. Following that, the Malaysian government implemented a Movement Control Order (MCO) as an immediate preventive measure to break the chain of infection. To overcome the issue, scientists have developed new specialised vaccines to curb the spread and reduce the likelihood of severe effects from the infection in people taking it. In Malaysia, several brands of vaccines are available, and vaccine-receivers are reported to experience side effects after the vaccination and varying degrees of severity of pain. A cross-sectional survey was performed using a self-administered anonymous online questionnaire from February to June 2022. The questionnaire was distributed to Malaysian citizens who are 18 years old and above, and the results were evaluated using descriptive analysis and the Chi-Square Test. The result was analysed using SPSS to show the socio-demographics of respondents, the severity of side effects from different brands of vaccines, and the association between gender, age, and type of brands of vaccines. Most of the respondents who received Pfizer-BioNTech had severe side effects compared to the other brands of vaccines. There was also a significant association between gender, age, severity level, and type of brands of vaccines.